SUITABLE PRIVATE DATA SHARING FOR GOVRNMENT MANAGEMENT UNDER THE PERSONAL DATA PROTECTION ACT - Deeod, Pongmanut; Payutto, Phrakhruwinaithon Worachad; Chaiyadat, Parichat; Boonnadee, Phramaha Chaichana (Journal of MCU Nakhondhat, 2022)
The purpose of this article is to investigate the suitable way to share personal data for government management under private data preservation because private data is a basic human right that the government should take care of as a citizen’s warranty. However, when the government intends to be transformed into a digital government in which all citizens’ data must be associative or well-managed between each department to be analyzed, planned, and transformed into suitable policy for citizens, it can be seen that there is still no clear format to standardize data sharing method in the government sector when private data prevention in case that there is data sharing in Thailand. Therefore, it is needed to be considered with international law which can be found that there must be direct permission from the data owner before sharing or using the private data in Japan, unless there is an emergency exception related to public health, only necessary data can be used in that circumstance. Singapore has divided the private data transfer method into 2 methods, 1) measure to preserve private personal data for the citizens, and 2) measure to share the private personal data abroad. Moreover, the European Union group has divided the personal data sharing method into 2 cases which are 1) Sharing personal data with a person or a third party for a common purpose within European Union, and 2) Sharing that is related to European Union or international organization personal data transfer. Therefore, Thailand has also considered this personal data preservation format.